2021
DOI: 10.3390/ijerph18147381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olympic Combat Sports on Older Adults’ Health Status: A Systematic Review

Abstract: The aim of this systematic review was to analyse the studies centered on the effects of Olympic combat sports (OCS [i.e., boxing, fencing, judo, karate, taekwondo, wrestling]) on older adults’ physical-functional, physiological, and psychoemotional health status. The review comprised randomised-controlled trials with OCS interventions, including older adults (>60 years), and measures of physical-functional, physiological, and/or psychoemotional health. The studies were searched through SCOPUS, PubMed/MEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 52 publications
3
36
0
Order By: Relevance
“…The main result of our review indicates that interventions based on OCS produce beneficial changes and an improvement trend with a small and moderate ES in HRQoL in both male and female, healthy participants, participants with Parkinson's disease, and participants with breast cancer. This result reinforces the scientific literature that has reported a positive impact of martial arts and combat sports on the health status in different population groups (Bu et al, 2010;Origua Rios et al, 2018;Moore et al, 2020;Valdés-Badilla et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The main result of our review indicates that interventions based on OCS produce beneficial changes and an improvement trend with a small and moderate ES in HRQoL in both male and female, healthy participants, participants with Parkinson's disease, and participants with breast cancer. This result reinforces the scientific literature that has reported a positive impact of martial arts and combat sports on the health status in different population groups (Bu et al, 2010;Origua Rios et al, 2018;Moore et al, 2020;Valdés-Badilla et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study showed that the 12-week Taekwondo self-defense training intervention positively improved physical fitness and was effective in modifying oxidative stress and levels of inflammation in postmenopausal women. The findings of this study support the results of a systematic review that concluded that Olympic combat sports, including Taekwondo, improved the physical-functional, physiological, and psychoemotional health of the elderly population [20].…”
Section: Discussionsupporting
confidence: 86%
“…Such a scenario could provide the opportunity to promote PA that requires a limited number of participants in reduced spaces for its practice, such as Olympic combat sports (OCS). In this context, OCS (boxing, fencing, judo, karate, taekwondo, and wrestling) are PA strategies that allow the development of sports practice individually or in pairs in confined spaces through low-impact dynamic actions with moderate to vigorous intensities using the upper and lower limbs through attack and defense movements, choreographies or specific forms of the disciplines and that can be practiced without contact [ 19 , 20 ]. Likewise, OCS include education about falls and exercises to face them [ 21 ] within their basic primary contents and achieve an adherence greater than 80% in older adults who practice OCS [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, OCS (boxing, fencing, judo, karate, taekwondo, and wrestling) are PA strategies that allow the development of sports practice individually or in pairs in confined spaces through low-impact dynamic actions with moderate to vigorous intensities using the upper and lower limbs through attack and defense movements, choreographies or specific forms of the disciplines and that can be practiced without contact [ 19 , 20 ]. Likewise, OCS include education about falls and exercises to face them [ 21 ] within their basic primary contents and achieve an adherence greater than 80% in older adults who practice OCS [ 19 ]. To the best of our knowledge, no review has attempted to summarize the currently available literature regarding the potential effects of OCS on balance, fall risk, or falls in older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation